Influence of contraceptive pill and menstrual cycle on serum lipids and high-density lipoprotein cholesterol concentrations. - Demacker, P N (1982)
The fluctuations of serum lipid and lipoprotein concentrations within one cycle were studied both in women using and not using oral contraceptives. High-density lipoprotein cholesterol decreased significantly from 1.47 mmol/l (57 mg/100 ml) to 1.30 mmol/l (50 mg/100 ml) during one contraceptive cycle in eight women and rose again to the initial value during the pill-free days. The mean concentration of total cholesterol also fell significantly as a result of the decrease of high-density lipoprotein cholesterol and of a not significant decrease of low-density lipoprotein cholesterol. The mean serum triglyceride concentration did not change significantly. The fluctuations in the concentration of serum lipids and lipoproteins in 10 women not using oral contraceptives were smaller than in the women using oral contraceptives and no significant changes in the concentrations were found during one cycle. Thus, high-density lipoprotein cholesterol concentration decreases during each contraceptive cycle. The time of blood sampling during the cycle is, therefore, of vital importance in interpreting the effect of oral contraceptives on high-density lipoprotein cholesterol. In women not using oral contraceptives blood can be sampled on random days during the cycle.